Development of a tomographic reconstruction method for axisymmetric Dα emission profiles in the ITER plasma boundary. (30th September 2020) - Neverov, Vladislav S; Khusnutdinov, Radmir I; Alekseev, Andrey G; Carr, Matthew; De Bock, Maarten; Kukushkin, Alexander B; Lovell, Jack; Meakins, Alex; Pitts, Richard; Polevoi, Alexei R; Veshchev, Evgeny
Abstract: A tomographic method for reconstructing the axially symmetric Dα emission profile in the ITER scrape-off layer and divertor from Dα intensity measurements in the fields of view (FoV) of Vis/IR TV and Divertor Impurity Monitor diagnostics is under development. The method takes into account the strong background signal due to stray light from divertor produced by reflections from the metal wall of the vacuum chamber. The method allows to filter out the reflections in Dα signals measured in the main chamber. The accuracy of this method is tested within the framework of a synthetic diagnostic, which uses the Raysect and Cherab numerical codes for ray-tracing simulations. The Dα emission profiles, simulated with the SOLPS and OEDGE codes, are used as synthetic experimental data. Uncertainty in light reflection properties of the first wall (FW) is the major factor affecting the accuracy of the Dα emission reconstruction. The dependence on the uncertainty in the FW surface roughness and on the ratio of diffusive to specular reflection of the error in recovering useful Dα signals (the direct light without reflections) in the FoV of the ITER main chamber H-alpha and Visible Spectroscopy Diagnostic is obtained.